Asymmetric supercapacitor based on vanadium disulfide nanosheets as a cathode and carbonized iron cations adsorbed onto polyaniline as an anode. (10th January 2018) - Rantho, M.N.; Madito, M.J.; Ochai-Ejeh, F.O.; Manyala, N.
Abstract: VS2 nanosheets electrode material was successfully synthesized by the hydrothermal method, and the electrode material (C-Fe/PANI) based on the carbonization of Fe cations adsorbed onto polyaniline (PANI) was directly synthesized on a nickel foam (current collector) by pyrolysis of the iron-PANI mixture coated on nickel foam in a tube furnace under the N2 atmosphere. The structural and morphological characterization of the as-synthesized electrode materials was carried out using X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FT-IR) spectroscopy and scanning electron microscopy (SEM). The electrochemical behavior of each working electrode was analyzed in a three-electrode cell configuration using 6 M KOH electrolyte, and thereafter, a hybrid (asymmetric) device was successfully fabricated using VS2 nanosheets as the positive electrode and C-Fe/PANI as a negative electrode. The fabricated VS2 //C-Fe/PANI asymmetric device was found to perform at a high applied potential difference of 1.7 V in 6 M KOH. At a current density of 2 A g −1, this device exhibited high energy and power densities of 27.8 Wh kg −1 and 2991.5 W kg −1 respectively. In addition, a VS2 //C-Fe/PANI device showed excellent cycling stability with 95% capacity retention over 10, 000 galvanostatic charge-discharge cycles at a current density of 5 A g −1 . Highlights: VS2 nanosheets electrode material was synthesized by the hydrothermal method. C-Fe/PANI was synthesized on nickel foam by pyrolysis of the iron-PANI mixture. The device was fabricated using VS2 as a cathode and C-Fe/PANI as an anode. VS2 //C-Fe/PANI asymmetric device exhibited good electrochemical performance.